Analisis Riset Produk Keripik Tempe - Rian Oki Firmansyah; Syamsul Hidayat (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Tempeh chips are a snack made from tempeh. This type of snack is loved by most Indonesian people, several regions in Indonesia make tempeh chips as a typical souvenir from that region. Unstable economic conditions such as in Indonesia can cause people's livelihoods to decline, forcing producers to be more creative in producing product. Tempe chips craftsmen are one of the mainstays of Indonesia's agricultural industry. the activity of tempe chips craftsmen is an effort taken by the Indonesian government to overcome the problems of unemployment and poverty. In this research study, research on the production of tempeh chips has been carried out by many researchers. Some results from related previous research are as follows: Leni Nuraeni's first research (2017) states that marketing strategy is a combination of four variables, namely product, price, promotion and distribution, a product is everything that can be offered on the market and also meets needs. Consumer price is the sales value set by the producer for something that the consumer buys based on the desire to get what they want. Promotion is a type of communication that can provide explanations to consumers. Distribution is a strategy that is closely related to the producer's efforts to distribute the product so that it reaches consumers. . The method used in this research is quantitative or statistical. Quantitative research methods are methods used for research on certain populations or samples. Thus, this approach will allow analysts to find out the extent of research on tempeh chips products. Tempe chips craftsmen are one of the mainstays of Indonesia's agricultural industry. The activity of tempeh chips craftsmen is an effort taken by the Indonesian government to overcome the problem of unemployment and poverty. More people like tempeh chips products, namely women, 24 respondents compared to men.